Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1038/bjc.1994.84
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of leukaemia cell proliferation by folic acid–polylysine-mediated introduction of c-myb antisense oligodeoxynucleotides into HL-60 cells

Abstract: Summary The inhibitory effect of c-myb antisense oligodeoxynucleotides (ODNs) conjugated to folic acid (FA) on HL-60 cell proliferation was examined. Folic acid was covalently linked to a polylysine chain and purified by gel chromatography. Sterile FA-polylysine was complexed with c-myb sense and antisense. Exposure of HL-60 cells to the FA-polylysine-c-myb antisense ODN complex resulted in a down-regulation of c-myb expression and a greater inhibition of proliferation than that obtained using free ODNs. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…Similar eects have been observed with HL-60 and several other myeloid leukemia cell lines where antisense inhibition of c-myb blocked their entrance into S phase resulting in a block to their proliferation. These ®ndings suggested that c-myb proto-oncogene is required for maintenance of proliferation and plays a direct role in cell cycle control of hematopoietic cells without aecting their dierentiation status (Anofossi et al, 1989;Citro et al, 1992Citro et al, , 1994. However, in another study, c-myb-antisense-treated HL-60 cells differentiated only into monocytes but not into granulocytes indicating that granulocytic dierentiation, unlike monocytic dierentiation, requires c-myb-mediated proliferation (Ferrari et al, 1990).…”
Section: Myb As a Regulator Of Proliferationmentioning
confidence: 98%
“…Similar eects have been observed with HL-60 and several other myeloid leukemia cell lines where antisense inhibition of c-myb blocked their entrance into S phase resulting in a block to their proliferation. These ®ndings suggested that c-myb proto-oncogene is required for maintenance of proliferation and plays a direct role in cell cycle control of hematopoietic cells without aecting their dierentiation status (Anofossi et al, 1989;Citro et al, 1992Citro et al, , 1994. However, in another study, c-myb-antisense-treated HL-60 cells differentiated only into monocytes but not into granulocytes indicating that granulocytic dierentiation, unlike monocytic dierentiation, requires c-myb-mediated proliferation (Ferrari et al, 1990).…”
Section: Myb As a Regulator Of Proliferationmentioning
confidence: 98%
“…Molecules that have been targeted to tumors by conjugation to folic acid include radiopharmaceuticals (Wang et al, , 1997Mathias et al, 1996Leamon et al, 2002). enzymes for pro-drug activation (Lu et al, 1999), nanoparticles (Oyewumi and Mumper;2003), peptides, toxic proteins , immunologically potent haptens 2002b), antisense oligonucleotides (Citro et al, 1994;Wang et al, 1995), chemotherapeutic agents (Ladino et al, 1997), gene therapy vectors (Lee and Huang, 1996;Reddy et al, 1999Reddy et al, , 2002Leamon and Low, 2001), viruses (Lee and Low, 1994;Reddy and Low, 2000), and polymeric drug carriers and liposomes Gabizon et al, 1999). It is noteworthy that both a folate-targeted therapeutic drug and a folate-linked imaging agent are currently under evaluation in human clinical trials.…”
mentioning
confidence: 99%
“…This method has been used successfully to aid ON delivery in selected cell types (8 -11). For example, asialoorosomucoidpolylysine conjugates have been used to target ONs to HepG2 and chloramphenicol acetyltransferase cells (8,9), and transferrin and folic acid conjugates have been employed to aid ON delivery to rapidly growing cells such as HL-60 cells (10,11). In the lung, alveolar macrophages (AMs) represent a major target for dust-induced pulmonary fibrosis.…”
mentioning
confidence: 99%